Approach to the Formulation of the Variable Change Theorem - Armando Morales Carballo; Edgardo Locia Espinoza; José M. Sigarreta Almira; Ismael G. Yero (MDPI AG, 2021)
This research proposes a didactic strategy to enrich the assimilation processes of the change of variable theorem in solving the definite integral. The theoretical foundations that support it are based on the contributions of social constructivism, problem solving, and treatment of theorems. The practical validation of the strategy is carried out with students of the Higher Technical Level in Applied Mathematics at the Autonomous University of Guerrero.